ENT300 Fundamentals of Entrepreneurship Best Carwash Sdn. Bhd / Wan Faris Zain Bin Wan Ahmadi... [et al.] - Wan Ahmadi, Wan Faris Zain; Che Mohd Noor, Muhd Shahrin; Sahmad, Nadzirah; Michael, Michelle Eliza; Garam, Lemunai (2015)
Our company’s name is BEST CARWASH SDN. BHD, which consists of five members to form partnership. Each partner contributes particular amount of capital which has been agreed in the contract. The major business activity is car cleaning and polishing. Our premise is located Perumahan Fasa II. 93050, Petra Jaya, Kuching, Sarawak. The main reason we chose this area to open our business is because of the strategic location. We will provide the best and fast services to our customers. Besides that, we also provide a sundry shop which sells ice creams to the customers. This is one of the way to let our customers enjoy their time while waiting for their cars to be cleaned and detailed. Furthermore, all the profits from the sundry shop will be donated to the charity.